Stylistic Analysis of the Famous Persian Fable the Scorpion and the Tortoise - Jahan, Jennifar (LANGUAGE ART, 2023)
The term "stylistic analysis," which describes the procedure of discovering usage patterns in speech and writing, is used by linguists to assess the value and significance of texts in literary studies. Analysing a document's style is crucial to understanding the text, content and the function of language within it. This paper aims to provide a stylistic analysis of the well-known Persian fable The Scorpion and the Tortoise by dissecting its various literary and rhetorical elements. Any given stylistic study aims to either break down a language into its component elements or obtain an understanding of its meaning. Many literary and linguistic devices are used in this story to show irrationality, obsession, tension, and other themes that keep coming up. So, using the method of stylistic analysis, I will look into how the writer's choices contribute to creating particular meanings.